Alternativas de tecnologías limpias para el reemplazo del mercurio en la minería aurífera (2018)
80% of mining in Colombia is illegal, which brings serious environmental and socioeconomic problems. It affects fauna and flora, human health causing damage to the nervous, respiratory, immune, reproductive, hematological, gastrointestinal, cardiovascular and kidney systems. The presence of illegal armed groups in mining areas is a factor of displacement and / or forced labor in children and women. Additionally, the environmental damage caused in páramos (such as Santurbán and Pisba) is added, due to the granting of environmental licenses for gold mining. The techniques to extract gold in artisanal mining are rudimentary and the workers do not have extensive knowledge of the methods used, which is why it is a risk factor in mercury contamination.